Soil and litter invertebrates - Majer, Jonathan; Greenslade, P. (1988)
Soil and litter invertebrates are a large, but generally inconspicuous, component of the biota of mediterranean regions whose existence is of crucial importance to the functioning of these ecosystems. Some groups are involved in the regulation of nutrient cycles, the maintenance of soil structure or are linked through their herbivorous activities with the productivity and dynamics of plant communities. Other taxa play an important role in seed dispersal and survival, in pollination or they may provide an important food source for insectivores. It is therefore fitting that this volume includes a chapter which compares the soil and litter invertebrates of the various mediterranean regions.